2019
DOI: 10.1002/chem.201806074
|View full text |Cite
|
Sign up to set email alerts
|

Advantageous Interfacial Effects of AgPd/g‐C3N4 for Photocatalytic Hydrogen Evolution: Electronic Structure and H2O Dissociation

Abstract: Bimetallic AgPd nanoparticles have been synthesized before, but the interfacial electronic effects of AgPd on the photocatalytic performance have been investigated less. In this work, the results of hydrogene volution suggest that the bimetallic AgPd/g-C 3 N 4 sample has superiora ctivity to Ag/g-C 3 N 4 and Pd/g-C 3 N 4 photocatalysts. The UV/Vis diffuse reflectances pectroscopy,X -ray photoelectron spectroscopy, CO adsorption diffuse reflectance FTIR spectroscopy,a nd FTIR results demonstrate that in the AgP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 50 publications
(99 reference statements)
0
7
0
Order By: Relevance
“…Consequently, bimetal co‐catalysts with broad structural and chemical functionalization were intensively explored. In the work by Zou et al., [216] the interstitial electronics interactions made by the bimetallic Ag‐Pd/g‐C 3 N 4 catalysts are more active than Ag/g‐C 3 N 4 and Pd/g‐C 3 N 4 . The Ag‐Pd nanostructures ranging in diameter from 4 to 6 nm were uniformly attached to g‐C 3 N 4 via polyol reductions.…”
Section: Interfacial Engineering Design Of G‐c3n4mentioning
confidence: 97%
“…Consequently, bimetal co‐catalysts with broad structural and chemical functionalization were intensively explored. In the work by Zou et al., [216] the interstitial electronics interactions made by the bimetallic Ag‐Pd/g‐C 3 N 4 catalysts are more active than Ag/g‐C 3 N 4 and Pd/g‐C 3 N 4 . The Ag‐Pd nanostructures ranging in diameter from 4 to 6 nm were uniformly attached to g‐C 3 N 4 via polyol reductions.…”
Section: Interfacial Engineering Design Of G‐c3n4mentioning
confidence: 97%
“…For Ag nanoparticles, the LSPR with high intensity in a region of 390-410 nm is observed. In the case of AgPd alloy, the intensity of the peak's changes with a change in the Ag:Pd ratio, so that for a ratio of 1:1 compared to 2:1, the effect of LSPR shows a greater reduction, which can be due to charge transfer to the Ag NPs surface 37,[72][73][74] . XRD planes of the bulk g-C 3 N 4 , SLCN and AgPd alloy nanoparticles supported on SLCN with different Ag:Pd ratios were revealed in Fig.…”
Section: Photocatalytic Dehydrogenation Of Famentioning
confidence: 99%
“…Accordingly, in recent years, photocatalytic degradation of FA to CO 2 and H 2 has been broadly studied in the literature [31][32][33][34][35] . Recent reports have shown that the design and manufacture of conjugated semiconductor polymers due to their advantages such as constancy in aqueous-medium, visible light absorbency, intramolecular charge transition, the low expense is one of the effective strategies [36][37][38] . Supported semiconductors with visible light absorption can be used to modify the photocatalytic operation of heterogeneous metal based catalysts for photo-decomposition formic acid 31,32,35,39,40 .…”
mentioning
confidence: 99%
“…[16][17][18][19][20] Among them, one of the burgeoning applications of CDs is their use as multi-functional electrochemistry catalysts in various energy conversion processes. Besides, CDs are also oen employed as a catalyst support to anchor metals, 21 oxides, 22,23 nitrides, etc. in electrochemistry.…”
Section: Introductionmentioning
confidence: 99%